ПОЭТИЧЕСКОЕ В ЖАНРЕ СКАЗКИ (На материале сопоставительного исследования каракалпакских и европейских народных сказок) - Саитова, З.К. (SCIENCE and SOCIETY, 2017)
The article deals with the comparative study of folklore works of the English and Karakalpak people, a great attention is paid to the poetics of fairy tales, created at different periods many years ago. The author investigated the personages and plot-ideological content of the English and Karakalpak fairy tales and found out that they are rich in expressive means and stylistic devices providing the high lyricism of the literary heritage of our off-springs-the poetics of a fairy tale genre.